Fedir Kindratovyč Vovk: una vita per l’antropologia - Tamara Mykhaylyak (EtnoAntropologia)
This paper recounts the life of Fedir Kindratovyč Vovk who is now considered the founder of Ukrainian Anthropology. His numerous travels and long stays in Europe allowed him not only to extend his anthropological and ethnographic studies while refining research methodologies, but also become a crucial reference point for the dissemination of scientific knowledge abroad. Great emphasis is therefore, placed on the last thirteen years of his life, a period during which Vovk devoted himself to the creation of the School of Anthropology in Saint Petersburg, the cradle of a new cultural era that has permanently marked, ever since, the future of russian anthropologists.